Cross-domain management system of real estate sales information based on blockchain. (26th January 2023) - Xue, Shu; Wei, Simin
In the existing real estate sales information management system, the efficiency of information cross-domain management is low, and the information security is poor. The whole architecture of real estate sales information system includes sales information collection module, intelligent contract execution module and real estate information encryption module. The discrete wavelet transform method is used to fuse similar data, and the intelligent contract is designed according to the data fusion results, and all sales information is encrypted. Then the trust model of blockchain certificate authorisation centre is designed, and the final result is verified with real estate sales information access cross-domain authentication and real estate sales information cross-domain management system design. The experimental results show that the safety factor of the system data designed in this paper can reach 0.99, and the system response delay is about 0.5 s.